High-performance electrochromic films with fast switching times using transparent/conductive nanoparticle-modulated charge transfer. Issue 38 (25th September 2019) - Yun, Junsang; Song, Yongkwon; Cho, Ikjun; Ko, Yongmin; Kwon, Cheong Hoon; Cho, Jinhan
Abstract : Facile charge transfer-induced structural/interfacial designs for high-performance transition metal oxide-based electrochromic films. Abstract : One of the most critical issues in electrochromic (EC) films based on transition metal oxides such as tungsten oxides (WO x ) is their poor charge transfer property, which is closely related to EC performance. Herein, high-performance EC films with enhanced charge transport are prepared using small-molecule linkers and transparent/conductive nanoparticles (NPs). In this work, oleylamine (OAm)-stabilized WO2.72 nanorods (NRs) and OAm-stabilized indium tin oxide (ITO) NPs are layer-by-layer (LbL)-assembled with small-molecule linkers (tris(2-aminoethyl)amine, TREN) using a ligand-exchange reaction between bulky/insulating OAm ligands and TREN molecules. In this case, there is only one TREN layer between neighboring inorganic components (WO2.72 NRs and/or ITO NPs), resulting in a dramatic decrease in the separation distance. This minimized separation distance as well as the periodic insertion of transparent/conductive ITO NPs can significantly reduce the charge transfer resistance within WO2.72 NR-based EC films, which remarkably improves their EC performance. Compared to EC films without ITO NPs, the formed EC films with ITO NPs exhibit faster switching responses (4.1 times in coloration time and 3.5 times in bleaching time) and a maximum optical modulation of approximately 55.8%. These results suggest that electrochemical performance, including EC performance, can be significantly improved through structural/interfacial designing of nanocomposites.